Relationship between plasma 17-beta estradiol on the day of estrus and number of viable embryos in Bos indicus (Nellore) cows superovulated with FSH. - Gradela, A. [UNESP]; Esper, C. R. [UNESP]; Rosa-e-Silva, A. A. [UNESP] (My University, 1994)
Thirteen cows, Bos indicus, of the Nellore breed were superovulated with 22 mg of follicle stimulating hormone (FSH) administered by intramuscular route during four consecutive days (D10, D11, D12 and D13), starting on the 10th day of the estrous cycle (day 0 = estrus). Prostaglandin (PGF2 alpha, 1.0 mg, im) was administered on D12, 48 h after the first FSH injection, for the induction of estrus on D14, when artificial insemination was performed. Seven days later (D21 of the cycle), embryos were collected, and evaluated, and the ovarian response was estimated on the basis of number of corpora lutea determined by rectal palpation. Blood samples were obtained for the determination of plasma 17-beta estradiol on D10, D11, D12, D13, D14 and D21 and plasma progesterone on D14 by RIA. The donors were divided into two groups according to progesterone levels on D14, the day of the induced estrus (GI: P4 < or = 1.00 ng/ml, N = 5 and GII: P4 > 1.00 ng/ml, N = 8). A linear positive correlation was observed between plasma 17-beta estradiol concentration on the day of estrus and viable embryo number. We conclude that plasma 17-beta estradiol and progesterone concentrations on the day of estrus can be used to predict the viability of embryos recovered from Nellore cows superovulated with FSH.